2022
DOI: 10.1038/s41598-022-15029-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between orthostatic hypotension and recurrence of benign paroxysmal positional vertigo

Abstract: Blood pressure is maintained by a combined mechanism of the baroreceptor reflex and the vestibulosympathetic reflex. This study is intended to verify the hypothesis that the orthostatic hypotension (OH) seen when benign paroxysmal positional vertigo (BPPV) occurred may act as a factor that affects the recurrence of BPPV. The subjects of present study were selected from among 239 patients diagnosed with idiopathic BPPV. The average age of the group with OH was 59.3 years, and the age of the group without OH was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Considering that most of these orthostatic dizziness patients were diagnosed by changes in blood pressure or heart rate in the tilt table test, physicians should also pay attention while taking their history to whether pediatric patients complain of dizziness while changing to the upright position or lying/bending down. The relationship between orthostatic dizziness and BPPV is unclear but recent studies have shown the correlation between BPPV-induced otolith organ hypofunction and transient orthostatic hypotension [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that most of these orthostatic dizziness patients were diagnosed by changes in blood pressure or heart rate in the tilt table test, physicians should also pay attention while taking their history to whether pediatric patients complain of dizziness while changing to the upright position or lying/bending down. The relationship between orthostatic dizziness and BPPV is unclear but recent studies have shown the correlation between BPPV-induced otolith organ hypofunction and transient orthostatic hypotension [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…When the vestibular evoked myogenic potential (VEMP) response was absent, the diastolic blood pressure dropped significantly at 1 min of active standing [ 9 ]. Furthermore, orthostatic hypotension (OH) accompanying benign paroxysmal positional vertigo (BPPV) affects the recurrence of BPPV [ 10 ], and utricular dysfunction is associated with OH [ 11 ]. The current study hypothesized that if otolith organ acts complementarily with the autonomic nervous system to maintain blood pressure, blood pressure variability may affect otolith organ.…”
Section: Introductionmentioning
confidence: 99%